Regional Labor Market Developments in Transition - Huber, Peter (World Bank, Washington, DC, 2012)
The author analyzes regional labor market disparities in transition by presenting some data and summarizing existing literature. He finds that large and persistent regional labor market disparities developed in virtually all transition countries and that there is some evidence of polarization. Differences in starting conditions and market access seem to be the major reasons for regional divergence in transition. Furthermore, regional wages are only slightly more flexible than in many European Union labor markets, interregional migration is low, and capital seems to move toward high wage and low unemployment urban centers rather than to the most backward regions. Policy should thus take a long-run perspective on the existing regional disparities, focus on removing barriers to mobility, review existing institutions for implementing regional policy, and aim at a close coordination of regional and labor market policy instruments.